ADOLESCENT MENTAL HEALTH DURING THE COVID-19 PANDEMIC IN PAPUA - Suriyani (Melati Institute, 2023)
Since the end of 2019, the Covid-19 pandemic has been experienced by various countries, including in Indonesia. Measures to prevent the spread of the Covid-19 pandemic have an impact on physical activity restrictions and the policy of implementing Distance Learning (PJJ) for students starting from elementary school to tertiary level. The purpose of this study is to get a picture of adolescent mental health during the Covid-19 pandemic and the role of sociodemographic factors in influencing adolescent mental health. The study involved 205 participants aged 15-18 years. Data was obtained using the General Health Questionnaire (GHQ-12) self-assessment measurement tool that has been validated in Indonesia. The results showed that as many as 59.5% of adolescents experienced psychological problems in the form of psychological distress and social dysfunction. Adolescent girls and adolescents who experience changes in sleep hours have a greater tendency to experience psychological problems. So, during the pandemic, adolescent girls need more attention than men and sleep patterns also need to be considered so as not to have an impact on psychological distress and social dysfunction during the pandemic.